Glutathione S–Transferase Activity of Human Erythrocytes Incubated in Aqueous Solutions of Five Antimalarial Drugs - Chikezie, Paul Chidoka (Free Radicals and Antioxidants)
Levels of human erythrocyte glutathione S-transferase (GST) activity were ascertained in the presence of separate increasing concentrations (0.2, 0.4, 0.6, and 0.8 mg% w/v) of five antimalarial drugs {Pyrimethamine/Sulphadoxine (PS), Halofantrine-HCl (H-HCl), Quinine, Artemether/umefantrine (AL) and Chloroquine Phosphate (CP)} in vitro. Determination of erythrocyte GST activity was carried out by spectrotrophotometric method with the standard substrate (1-chloro-2, 4-dinitrobenzene) and co-substrate (reduced gluthathione) at maximum absorbance (λmax) = 340 nm. Human erythrocyte GST activity ranged between 3.27 ± 0.13 and 3.40 ± 0.05 iu/gHb. The addition of increasing concentrations of four antimalarial drugs to assay mixture engendered decreased levels of GST activity in a concentration dependent manner, which was in the order: CP > AL > Quinine > PS. Specifically, 0.8 mg% CP exhibited the highest capacity to cause decreased GST activity from values of 3.41 ± 0.06 to 2.18 ± 0.09 iu/gHb, representing 33.7% relative inhibition of GST activity. In contrast, concentrations of H-HCl between 0.2 and 0.6 mg% caused elevation of GST activity above the values of the control samples. However, the increased levels of GST activity was not significantly different (p > 0.05) compared with the control samples. The five antimalarial drugs exhibited variable capacities to alter human erythrocyte GST activity, which suggest the capability of these drugs to perturb the redox status of human erythrocytes.
Keywords: Antimalarials; 1-chloro-2; 4-dinitrobenzene; erythrocytes; glutathione-S transferase